2018
DOI: 10.1108/bpmj-10-2016-0221
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factors influencing knowledge management system (KMS) adoption in small and medium enterprises SMEs

Abstract: Purpose The potential for the adoption of a knowledge management system (KMS) is becoming a crucial matter in small and medium enterprises (SMEs); however, there is a scarcity of studies related to KMS adoption in SMEs. Therefore, the purpose of this paper is to advance further our understanding of the factors that influence the KMS adoption process among SMEs. Design/methodology/approach The collected sample size was 247 respondents. For statistical analysis, Smart partial least square (PLS) (a structural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 170 publications
(181 reference statements)
4
33
0
8
Order By: Relevance
“…Abubakar et al (2017) added that "knowledge management involves several elements like human resources practices, technology, culture and organizational structures; which makes it a meticulous approach toward the optimization of a firm's knowledge economy as well as innovations" (pg.13). Implementation of KMS is not just a technological concern but also involve human factor (Shrafat, 2017). Which could be translated into knowledge-based HRM practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abubakar et al (2017) added that "knowledge management involves several elements like human resources practices, technology, culture and organizational structures; which makes it a meticulous approach toward the optimization of a firm's knowledge economy as well as innovations" (pg.13). Implementation of KMS is not just a technological concern but also involve human factor (Shrafat, 2017). Which could be translated into knowledge-based HRM practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hitherto, the research on KM has been conducted extensively, however mainly focuses on LEs, there is an obvious insufficiency of research on key KM elements in MEs (Shrafat, 2018;Massaro, et al, 2016;Serenko, 2013;Durst and Edvardsson, 2012). Due to the existence of resource constraints faced by MEs as well as the differences of MEs to LEs (Shrafat, 2018;Brink and Madsen, 2015;Cohen and Kaimenakis, 2007;Durst and Edvardsson, 2012), the KM approaches in MEs may have their own characteristics and be different from that in LEs in the content, implementation form and suitable industrial settings, which deserve an extensive exploration (Shrafat, 2018;de Guimarães, et al, 2018;Massaro, et al, 2016;Durst and Edvardsson, 2012). Nevertheless, in this research for a concentrated investigation and also due to the salient importance of manufacturing MEs (Pitelis and Antonakis, 2003), the authors do not focus the research on KM as a whole entity and in a full industrial spectrum of MEs; instead they explored a main element of KM -knowledge identification and only in manufacturing MEs and focusing on QI as a general background context.…”
Section: Knowledge Management (Km) Issues In View Of Mesmentioning
confidence: 99%
“…Many MEs have been committed towards implementing appropriate QI strategy to pursue operations excellence (Kumar, et al, 2016). While due to the diversity of MEs themselves and their difference to the large enterprises (LEs), and also owing to organisation size's heavy impact on the processes of KM (Shrafat, 2018), as well as a common situation faced by MEs -resources constraint, not all the currently existing knowledge of QI strategies and techniques (majority of which are with a focus on LEs) is suitable for or can be applied by MEs (de Guimarães, et al, 2018;Brink and Madsen, 2015;Durst and Edvardsson, 2012); therefore, MEs strongly need to know exactly what QIK is relevant to them and why, and more importantly how to obtain it or create new QIK in case of not currently existing, all these can be realised through QIK identification. However currently there is a dearth of theoretical comprehension on QIK identification issues to guide the MEs' practice for realising the aforesaid need; a circumstance as such highlights that it is highly necessary to explore the QIK identification, which is an important part of MEs' business operations (Centobelli, et al, 2019;Massaro, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also showed that various managerial processes and tools employed by businesses to promote innovation have an impact on their level of innovation. Therefore, it was decided to add the following control variables: Business activity aimed at acquiring external knowledge (Caloghirou et al 2004;Harel et al 2019b); external collaborations for innovation purposes (Harel et al 2019b;Kaufmann and Schwartz 2008;Kaufmann and Schwartz 2009;Öberg and Alexander 2018;Stanko et al 2017); managerial processes for utilizing knowledge (Ahluwalia et al 2017;Caloghirou et al 2004;Harel et al 2020a;Shrafat 2018); and an organizational culture that encourages innovation (Harel et al 2020b;Skarzynski and Gibson 2013;Terziovski 2010).…”
Section: Research Variablesmentioning
confidence: 99%